Integration of Islamic Values in STEM Teaching (Science, Technology, Engineering, Mathematics) - Judijanto, Loso; Yusniar, Yusniar (Westscience Press, 2025)
The integration of Islamic values into the learning of STEM subjects aims to align modern education with ethical and spiritual principles for holistic learning experiences. This study systematically reviews 25 manuscripts from the Scopus database to analyze curriculum designs, pedagogical strategies, educational outcomes, and challenges in incorporating Islamic values into STEM education. The findings have identified the inculcation of ethical values, contributions of Muslim scholars in history, and project-based learning as some of the effective approaches. Other positive impacts are increased motivation, ethical awareness, and all-round development of students, while resource limitation and teacher preparedness remain some of the major barriers. This study informs educators and policy-makers who might want to consider culturally relevant and ethically anchored STEM education frameworks.